last day (1173 days later) » 

20:01
room topic changed to Integrated Circus: 3 rings without identity (no tags)
in Mathematics, 50 mins ago, by Nicolás Castellanos
$8^{-3x}\cdot 2^{x+1}=4^{x+2}$
we have $-2^{-8x+4}x+1=-2^{2x+7}x+1$
The Math room was getting agitated.
20:04
@NicolásCastellanos no you don't have that
you told me that multiply the two sides by -8x+1
lets start from the beginning
$2^{-8x+1}=2^{2x+4}$ is what we are starting with
I suggested multiplying both sides by $2^{8x-1}$
$2^{-8x+1}\cdot2^{8x-1}=2^{2x+4}\cdot2^{8x-1}$
the left side is: $-2^{-8x+4}x+1$
why
$2^{-8x+1}\cdot -8x+1$
=
20:07
@NicolásCastellanos NO
ADD the exponents
you told me multiplying the sides by 8x+1, and that confused me
wait
$2^0=2^{10x+3}$
@NicolásCastellanos that is NOT what I said
in the other chat
well lets forget it
20:09
3 mins ago, by robjohn
I suggested multiplying both sides by $2^{8x-1}$
in Mathematics, 26 mins ago, by robjohn
Why not multiply both sides by $2^{8x-1}$?
the left side: 2^(-16x-2)?
the sum of the exponents on the left side is $0$
20:11
$(-8x+1)+(8x-1)$
ah
im reading bad
the right side
2^(10x + 5
$(2x+4)+(8x-1)=???$
2^0 = 1
2^(10x+3) = 1
10x+3 = 0
20:13
$10x+3=0$
yes
and now clean the expression
$x=-\frac3{10}$
10 to divide
20:15
yes
next
$3^{2x}+3^x-12=0$
that equation already has the "= 0"
i can solve it joining the two 3 bases?
or the form is cuadratic formula?
i will make it my self
i have this
$x=\frac{\left(-3+-\sqrt{153}\right)}{6}$
correct?
That is a quadratic equation, so you would use the formula
but what you get is $3^x=\frac{-1\pm\sqrt{1^2-4\cdot(-12)}}{2}$
if $y=3^x$, the equation is then $y^2+y-12=0$ ($a=1,b=1,c=-12$)
So...
20:33
im sorry i was busy
but a = 3, b = 3, and c = -12
simplify the equation?
nono 3^x
i can understand
why 3^x and no x?
You are solving $y^2+y-12=0$ and $y=3^x$
I think what you mean is correct, but the way you've written it has problems. $y^2=3^{2x}$
which would be y^2=3^(2x)
otherwise people might think you mean y^2=9x
but yes, $y^2=3^{2x}=9^x$
$y=\frac{\left(-1+-\sqrt{49}\right)}{2}$
sqrt(49) = 7
with +, y = 3
3^x = 3
x = 1
$3^2+3^1-12 = 0$
now with minus
You won't be able to get a negative number for $3^x$ with real $x$, so you can ignore the other root from the quadratic equation
yes...
someone in the math chat told me that i need the two solutions
@NicolásCastellanos not with real numbers. With complex numbers you could have many solutions
So whoever said you needed two was not correct.
$3^x=-4$ has no real solutions
@NicolásCastellanos I said:
in Mathematics, 4 hours ago, by PM 2Ring
@NicolásCastellanos Because! You always need to find both solutions if the equation is a quadratic. Sometimes, there will be no real solutions. Sometimes there will be two identical solutions, eg $(x-3)^2=0$. In some problems, one of the solutions may be invalid, eg because you only want positive solutions, or integer solutions. But you need to find those solutions before you decide what to do with them.
20:46
with minus, x=log_3(4)
or 1.26
No, they said you need to find both solutions of the quadratic. but then they said some of the solutions might be invalid.
And remember, a similar thing happened when we had $z=\pm\sqrt{125}$. We could ignore the negative solution because $z=x^2$
next equation
$3^{3x+1}=9\left(2^{x+3}\right)$
the right side can be simplified
to 18^(x+3)
then we can express in base 3
because 3*6 = 18
nono
18 cant be expressed with base 3
@NicolásCastellanos no
$3^{3x+1}=18^{x+3}$
20:51
$9\left(2^{x+3}\right)=3^2\cdot2^{x+3}$
because $9=3^2$
you cannot simply say that $a\cdot b^c=(ab)^c$
now the right side
make the multiplication
6^(2x+6)
20:54
what are you doing?
multiplying the right side
by what?
making that multiplication
3^2 * 2^(x+3
no you are not
The right side is $3^2\cdot2^{x+3}$
so what must i do?
20:56
You cannot combine them any further. That is not $a^xa^y=a^{x+y}$
you have $3^{3x+1}=3^2\cdot2^{x+3}$
now we can divide both sides by $3^2$, which is the same as multiplying them by $3^{-2}$
@robjohn that is we have
the left side is so 3 ^ ((3x+1) - 2)
21:00
yep
the right side
conmutative property
right?
sure
3^2 / 3^2 = 1
2^(x+3) / 3^2 =
that is true
isnt the same base
21:01
but you already had $3^2$ on that side
so is cancelled
and is 2^(x+3)
so you get $2^{x+3}$ on the right
i am understanding!!!
So you have $3^{3x-1}=2^{x+3}$
mmm
let me mean
or think
i dont know the word
let me use my brain
must be solved with ln
but i dont know how
21:06
Let's take the log_2 of both sides...
$(3x-1)\log_2(3)=x+3$
why from this form?
$log_2\left(3^{3x-1}\right)=log_2\left(2^{x+3}\right)$
no?
@NicolásCastellanos that brings the $x$s out from the exponent
yes.
and the other two?
is used to the base of the logarithms?
the base of the right side
@robjohn we have that
then..
wait
calculate the log2(3)?
no
the left side becomes
3log_2(3)x - log_2(3)
$3\log _2\left(3\right)x-\log _2\left(3\right)=x+3$
now add log_2(3) in both sides?
no
21:14
@NicolásCastellanos hang on a sec and let me look
i will take a break
wait me
$(3\log_2(3)-1)x=3+\log_2(3)$
to move all the $x$'s to one side and the rest to the other
so
whats next?
the next equation is more hard :(
now divide de both sides
by 3log_2(3)-1
$\frac{\left(3\log _2\left(3\right)-1\right)x}{3\log _2\left(3\right)-1}=\frac{3}{3\log _2\left(3\right)-1}+\frac{\log _2\left(3\right)}{3\log _2\left(3\right)-1}$
yes?
right?
$x=\frac{3+\log _2\left(3\right)}{3\log _2\left(3\right)-1}$
x = 1.22
next
$1.21^{5\left(x+1\right)}+1.1^{10\left(x+1\right)}=1.1$
too hard
simplify
$1.21^{\left(5x+5\right)}+1.1^{\left(10x+10\right)}=1.1$?
now what?
@robjohn ???
21:45
hi
jflkasdfjklsafjladskflaskflskfjsadlfjsadklfjasklflksflsfjlksdfjlkdjflksdjflkdsjfads
22:04
@NicolásCastellanos $121=11^2$, so $1.21=1.1^2$
22:14
OMG this room has been invaded!
@NicolásCastellanos that is correct
Yes. $1.21=1.1^2$
So apply the quadratic equation again
which is greater, $1.21^{5(x+1)}$ or $1.1^{10(x+1)}$?
I take it back. You don't need the quadratic equation
22:57
@NicolásCastellanos $log(1) = 0$
ok
whats the relation of a with b if log(a) + log(b) = 0
that means that log(ab) = 0
that means that ab = 1
that means that 1 / a = b
@NicolásCastellanos Correct

  last day (1173 days later) »